Immunological considerations for treating globoid cell leukodystrophy. Issue 11 (November 2016) - Karumuthil‐Melethil, Subha; Gray, Steven J.
Abstract : Globoid cell leukodystrophy (GLD, or Krabbe's disease) is a severe inherited neurodegenerative disease caused by the lack of a lysosomal enzyme, GALC. The disease has been characterized in humans as well as three naturally occurring animal models, murine, canine, and nonhuman primate. Multiple treatment strategies have been explored for GLD, including enzyme replacement therapy, small‐molecule pharmacological approaches, gene therapy, and bone marrow transplant. No single therapeutic approach has proved to be entirely effective, and the reason for this is not well understood. It is unclear whether initiation of a neuroinflammatory cascade in GLD precedes demyelination, a hallmark of the disease, but it does precede overt symptoms. This Review explores what is known about the role of inflammation and the immune response in the progression of GLD as well as how various treatment strategies might interplay with innate and adaptive immune responses involved in GLD. The focus of this Review is on GLD, but these concepts may have relevance for other, related diseases. © 2016 Wiley Periodicals, Inc.